大腦移植對於道德責任歸屬的挑戰: 人格同一性判準的反思: Challenges by Brain Transplantation: Criteria for Personal Identity - CHOU, Wanling (International Journal of Chinese & Comparative Philosophy of Medicine, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 當今社會， 作為治療方式的器官移植手術(organ transplantation)已經相當普遍。然而，如果大腦作為器官的一種，並且在技術上成為可能，那麼我們如何透過大腦的提供者和接收者的關係去界定人格同一性的問題？我們又如何在傳統的同一性的概念上去解釋道德責任的歸屬呢？本文主要探討大腦移植手術對於人格同一性判準的挑戰與可能的回應。筆者認為，西方傳統以來在探討關於人格同一性的概念時，多從生物層次的個體以及心理層次的自我來思考問題，並沒有跳脫個人的視角。文章試圖從儒家思想對人格同一性問題，探討跳脫西方既有的將人化約的思維脈絡來重新思考人格同一性判準。 Organ transplantation is now accepted as a common medical treatment. However, the potential for the transplantation of the brain, like any other organ, to become technically feasible gives rise to a series of ethical issues. This essay focuses on the challenges to the criteria for personal identity created by medical technology. Does transplantation preserve the integrity of personal identity? If not, how can we define moral accountability? The essay attempts to show that the traditional definition of personal identity in the West is both biologically and psychologically reductive, as it fails to deal with the issue of the preservation of personal identity in the case of brain transplants. The author argues for an alternative way (via the Confucian understanding of the person and relationality, for example) of responding to the new ethical challenges associated with brain transplantation. DOWNLOAD HISTORY | This article has been downloaded 301 times in Digital Commons before migrating into this platform.